Workshop Program Sekolah Tangguh: Penguatan Pendidikan Karakter Berbasis Kolaborasi Komunitas Belajar bagi Guru - Kusnaini Kusnaini; Dwi Priyo Utomo; Nana Liesdiana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Teachers need skills in understanding, designing, and implementing character-based learning that is aligned with the Merdeka Curriculum and the eight dimensions of the Pancasila Student Profile. This community service activity aimed to improve teachers’ competence in integrating character education through the Resilient School Program based on learning community collaboration. The activity was conducted offline for two weeks at SD Negeri Wonorejo 1, SD Negeri Wonorejo 2, and SD Negeri Wonorejo 4 in Malang City, involving 45 teachers as participants. The implementation method used a collaborative participatory approach through the stages of needs analysis, program planning, workshop implementation, evaluation, and follow-up. Data were collected through observation, pre-test and post-test, documentation, and reflective discussions, and were analyzed using descriptive quantitative and qualitative methods. The results showed an improvement in teachers’ competence across all indicators, including understanding the concept of character education, the ability to develop lesson plans or teaching modules integrated with character values, and the implementation of collaborative learning based on character education. The average increase in teachers’ competence reached 68.7%, which was categorized as high, with the highest improvement found in the collaborative learning implementation indicator at 76.1%. These findings indicate that teacher learning communities are effective as spaces for reflection, sharing best practices, and continuous professional development.